Evaluation of Toxicity of Some Tropical Flora, Clay and Permethrin against Sitophilus zeamais Motsch. on Stored Maize Grains - Kingsley Chidi Emeasor; Victor Nkwachi Nwakanma; David Nwazuo Enyiukwu (Universitas Sebelas Maret, 2022)
Weevil (Sitophilus zeamais Motsch.) is a vital arthropod pest of maize (Zea mays L.) grains and flours in traditional storage systems. The pest bore holes into stored grains reducing their nutrient contents germination potentials and contaminating produce with frass. Its control using synthetic insecticides such as permethrin is being downplayed due to eco-mammalian toxicity from pesticide residues. Therefore, this study evaluates the toxicities of some indigenous plants Ageratum conyzoides L., Cymbopogon nardus L., clay and permethrin, under laboratory conditions to the insect pest. Maize grains weighing 50 g were treated with the plant powders and the synthetic insecticide at five different levels 0.00; 1.25; 2.50; 3.75 and 5.00 g. Subsequently, 10 adult weevils in each vial were used to infest the 50 g maize grains. Each plant powder and permethrin's effectiveness was assessed by recording weevil mortality at 5, 7, 14, 21 and 28 days post-treatment. The damage indices recorded by the weevil perforation index (WPI), percentage of perforated and unperforated grains, and weight loss percentage were also considered. Permethrin proved most toxic, followed by clay at 5.00 g among all the treatments. A. conyzoides and C. nardus were less effective in controlling S. zeamais. In conclusion, clay can be used in the integrated management of S. zeamais to minimize synthetic insecticides.